Improving EFL students’ vocabulary acquisition: a phenomenological study on the use of the “DuoCards” mobile application - Fadlah Putri Sabila; Salmiah, Maryati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study investigates English as a Foreign Language (EFL) students’ perceptions of the “DuoCards” mobile application as a tool for vocabulary enrichment. Employing a qualitative research design with a descriptive phenomenological approach, data were gathered through questionnaires administered to 20 junior high school students, followed by in-depth interviews with five selected participants. The findings reveal seven key themes: (1) Usability and Features – DuoCards is perceived as user-friendly and effective in supporting vocabulary acquisition; (2) Accessibility – the application offers flexible access, though some students reported login issues; (3) Vocabulary Enrichment – visual stimuli and interactive elements aid in vocabulary retention; (4) Confidence in Communication – while the app increases motivation, its influence on spoken confidence remains limited; (5) Content Coverage – learners appreciate the comprehensive and regularly updated vocabulary topics; (6) Technical Challenges – occasional access issues, particularly during the login process, were noted; and (7) Feature Awareness – while interactive functions are available, a lack of user awareness may limit their optimal use. The results indicate that DuoCards has significant potential as a mobile-assisted language learning (MALL) tool. However, technical and pedagogical improvements are recommended to maximize its impact. Overall, DuoCards is endorsed as an effective supplementary platform for enhancing students’ vocabulary acquisition in EFL contexts.